Parasitic contamination of public squares in the City of João Pessoa, Paraíba (Research, Society and Development, 2021)
Animals can attend public places such as beaches, public squares and parks, which can result in public health problems. The soil contaminated by helminth eggs and larvae is a way of transmission, serving as an important indicator of the occurrence of cutaneous and visceral larva migrans. The aim of this study was to evaluate the potencial of zoonotic contamination of parasites in public squares sands of the city of João Pessoa, Paraíba - Brazil. Therefore, sand samples and feces were collected from dogs and/or cats 40 public squares, and subsequently analyzed. In the results, 95% (38/40) of the public squares analyzed were contaminated. Using the methods already mentioned, a total of 456 samples of feces and sand were analyzed and 208 were positive for helminthes. Of these 208 positive samples, 45.9% (200/436) were sand and 47.5% (8/17) were feces. In this study were found the eggs (62.4%) and larvae (30.9%) of Ancylostoma spp., eggs (0.26%) and larvae (5.5%) of Strongyloides spp., and eggs of Toxocara spp. (0.59%) and Dipylidium caninum (0.19%). The presence of different types of parasites have an important epidemiological significance, which indicates the existence of favorable environmental conditions for the development of these microorganisms, especially in relation to possible occurrence of cutaneous and visceral larva migrans. These results show that there is a risk to the health of the population that attends these environments without properly care.